Point of Care Ultrasound Used to Diagnose Nontyphoidal Endocarditis - Zahraa Yousef Alqallaf; Ossama maadarani; Mohamed Elsayed Elhabibi; Mohamad Abdelfatah; zouheir bitar (CINQUILL Medical Publishers Inc., 2024)
Point of care ultrasound (POCUS) can make an expedited diagnosis, which might lead to early correct management. POCUS should be used in a systemic and integrated approach to evaluate multiple organs in patients with sepsis and septic shock. We present a rare case of sepsis due to Salmonella endocarditis with abscess in which a POCUS examination led to expedited treatment.